A decade of robotics in lung cancer surgery - Louie, Brian E. (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Minimally invasive approaches to cancer surgery have been widely embraced by many surgical specialties and for many the less invasive approach is used preferentially. For thoracic surgeons, lung cancer and pulmonary lobectomy is the dominant oncologic procedure but open thoracotomy remains the most commonly used approach to lung cancer resection. Minimally invasive lobectomy using a video assisted approach or VATS was first reported nearly 25 years ago (1) and despite multiple studies demonstrating clear benefits adoption has been slower than anticipated.